2022
DOI: 10.14474/ptrs.2022.11.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Non-face-to-Face Class due to COVID-19 on Academic Stress and Back Pain in University StudentsThe Effect of Non-face-to-Face Class due to COVID-19 on Academic Stress and Back Pain in University Students

Abstract: Objective: In the present study, to determine the extent of academic stress and pain from sitting for a long time, we will use a questionnaire to examine the effects of non-face-to-face stress and back pain on college students who have conducted non-face-to-face lectures. Design: Survey researchMethods: A questionnaire was conducted using Naver foam to identify academic stress, attitude and time to listen to lectures, and the extent of back pain for college students who are experiencing non-face-to-face lectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Thus, art therapy and art making can serve as effective means of emotional expression for individuals with emotional or psychological difficulties, including those who have difficulty expressing their emotions directly (Wadeson, 1987;Malchiodi, 2005). By stimulating internal group interactions, art therapy delivers a platform for people to discuss life issues and improve their interpersonal relationship skills (Park, 2020), then reducing academic stress and deepening life satisfaction (Kim, 2022). Cho (2022) showed that painting-centered group art therapy can help foreign students enhance their self-awareness and expression, increase intimacy within the group, reduce stress in the community, and improve quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, art therapy and art making can serve as effective means of emotional expression for individuals with emotional or psychological difficulties, including those who have difficulty expressing their emotions directly (Wadeson, 1987;Malchiodi, 2005). By stimulating internal group interactions, art therapy delivers a platform for people to discuss life issues and improve their interpersonal relationship skills (Park, 2020), then reducing academic stress and deepening life satisfaction (Kim, 2022). Cho (2022) showed that painting-centered group art therapy can help foreign students enhance their self-awareness and expression, increase intimacy within the group, reduce stress in the community, and improve quality of life.…”
Section: Introductionmentioning
confidence: 99%